Designing Self-Management Features for Digital Islamic Spiritual Health Interventions for Adolescents with Sexual Behavior Problems - Mohd Noh, Mohd Amin; Mat Noor, Siti Fadzilah; Judi, Hairulliza Mohamad; Mat Zin, Nor Azan; @Ashaari, Noraidah Sahari (SCAD Independent, 2025)
Digital health interventions (DHIs) have the potential to provide culturally relevant, private support for adolescent sexual behavior problems (SBPs), yet few are designed for Muslim-majority contexts. In Malaysia, the absence of an Islamic-values-based self-management intervention (SmI) model limits the integration of faith-based principles in adolescent health interventions. This study applies the TUDER framework (Targeting and Understanding) to map existing DHIs and identify key features for an Islamic-values-based SmI design. A web search conducted from January to April 2024 identified 53 platforms across Malaysia and neighboring countries, categorized by service type and features. Semi-structured interviews with nine experts in adolescent health and Islamic spiritual interventions were analyzed thematically using Braun and Clarke’s six-step process. Seven key design features—privacy, relaxation, lighthearted tone, catchiness, humor, confidence-boosting, and infographics—emerged as critical for engaging adolescents in conservative contexts. These features align with Islamic psychospiritual principles like tazkiyah al-nafs (spiritual purification). This study proposes a conceptual SmI framework that integrates these features with persuasive system design, offering a novel approach for developing culturally grounded DHIs. The framework strengthens the theoretical foundation for Islamic-values-based interventions and can be adapted to similar settings in Muslim-majority countries.